Odpowiedź:
zad. 6
a)
po prawej: 3x
P = x(a+3) = ax + 3x
b)
po lewej: 8a
po prawej: 2ab
na dole: 4 + b
P = a(8+2b) = 8a + 2ab
c)
po lewej: 4ax
po prawej: 6a
na dole: 2x + 3
P = a(4x + 6) = 4ax + 6a
d)
po lewej: 4as
po prawej: 2s
na górze: 5
P = s(4a + 2b) = 10s + 4as
zad. 8
a)
2x(x-4)-5x =
2x*x-2x*4-5x =
2x²-4x-5x =
2x²-9x
b)
7x-3(x+8)=
7x-3*x-3*8
7x-3x-24=
4x-24
c)
2x(a-3)+4(x-2)=
2x*a-2x*3+4*x-4*2=
2ax-6x+4x-8=
2ax-2x-8
d)
-4x(5+2x)+2x(-2x-5)=
-4x*5-4x*2x-2x*2x-2x*5=
-20x-8x²-4x²-10x=
-30x-12x²
PS. Nie wiedziałam jak zaznaczyć podkreślenie dwiema kreskami, więc x² oznaczyłam jako pogrubienie